Hot-wire plasma enhanced chemical vapour deposition system for preparation of silicon carbide thin films / Aniszawati Azis - Aniszawati, Azis (2012)
This research offers insights on the function of a home-built plasma enhanced chemical vapor deposition (PECVD) system in the preparation of silicon carbide (SiC) thin films. The work started with designing and building a reaction chamber for the PECVD system that would utilize radio frequency (RF), direct current (DC) and hotwire (HW). The first phase of the work ensured that the PECVD system is capable of producing good quality and reproducible silicon carbide thin films via independent deposition techniques namely RF-PECVD, DC-PECVD and HW-CVD. The effects of methane to silane gas flow rate ratio on the deposition rate, optical energy gap, Si-C and Si-H bonding configurations and formation of any crystalline structures were investigated. Analytical study revolved around the results obtained from Optical transmission spectroscopy, Fourier transform infrared (FTIR) spectroscopy, micro- Raman scattering spectroscopy and X-Ray diffraction spectroscopy. Based on the findings from the first phase of the work, the research was then proceeded to the next phase of the work where a hybrid deposition technique comprising DC-PECVD and HW-CVD was introduced and applied. The study for these films involved the effects of applied DC voltage and the role of hydrogen in the growth and deposition process of silicon carbide thin films. Results of this work demonstrated that the optical energy band gap of the silicon carbide films prepared by all techniques could be increased by increasing the methane to silane gas flow rate ratio. These results were consistent with published results and the variation of the properties of the films was consistent with the deposition kinetics of silicon carbide. The system is tunable to produce silicon carbide films with a wide range of optical energy band gap from 1.63 eV to 3.26 eV. The film deposition rate is affected in contrary manners for different techniques and does not show direct effect on carbon incorporation nor crystallization of the film. However, by the multiple ranges of deposition parameters allowed by the system built in this work, a variety of silicon carbide thin film could be produced. RF-PECVD technique provides silicon rich amorphous silicon carbide films with deliberately high optical energy band gap. DC-PECVD technique displayed low deposition rate as compared to the other techniques but produces silicon carbide films with relatively high optical energy band gap and more ordered structure with traces of silicon nanocrystallites. Silicon carbide films prepared by HW-CVD technique exhibit enhanced properties such as increasing value of optical energy band gap and more amorphous structure with increased methane to silane gas flow rate ratio. The new HW-PECVD technique demonstrated in this system has succeeded in preparing silicon carbide thin films and provided a minimum optical energy band gap of 2.05 eV. The optical energy band gap could be increased by applying lower DC voltage. The new deposition system is also made feasible to hydrogen applications. It was observed that nanocrystallite structures were formed and were embedded in amorphous SiC film matrix with longer hydrogen surface treatment time.